Interactions between wear and corrosion on cast and sintered Ti-12Nb alloy in comparison with the commercial Ti-6Al-4V alloy - Caha, Ihsan (2020)
This work investigates the corrosion and tribocorrosion behavior of alpha + beta Ti-12Nb alloy processed by casting and sintering, in 9 g/l NaCl solution at body temperature, and compares the results with the commercial Ti-6Al-4 V alloy. Different electrochemical techniques were used to access the corrosion behavior. Tribocorrosion behavior was studied at open circuit potential under continuous and intermittent sliding, and at anodic potentiostatic condition under continuous sliding. Results revealed that Ti-12Nb alloys presented similar tribocorrosion behavior although the sintered one exhibited a better corrosion behavior. Nevertheless, Ti-6Al-4 V presented better overall degradation resistance than both Ti-12Nb alloys.